Selective Isolation of Bifidobacterium From Human Faeces Using Pangenomics, Metagenomics, and Enzymology - Yang, Shuanghong; Xie, Xinqiang; Ma, Jun; He, Xingxiang; Li, Ying; Du, Mingzhu; Li, Longyan; Yang, Lingshuang; Wu, Qingping; Chen, Wei; Zhang, Jumei (Frontiers in Microbiology, 2021)
Because Bifidobacterium is a difficult species to isolate, we applied metagenomics, pangenomics, and enzymology to determine the dominant glycoside hydrolase (GH) families belonging to Bifidobacterium in human faecal samples. Pangenomics results showed that the GH13, GH3, GH42, and GH43 families are highly conserved in Bifidobacterium. Metagenomic analysis of GH families in human faecal samples was performed, and the functions of these enzymes were predicted using SWISS-MODEL. We applied carbohydrates corresponding to their specific bifidobacterial enzymes as the main carbon sources for selective media, which promoted bifidobacterial growth while inhibiting the growth of other microorganisms. The highest proportion of Bifidobacterium was 89.39% ± 2.50% in medium with lactose as the main carbon source. Further, the species significantly varied among samples from different individuals. Results suggested that lactose and xylan might be prebiotics that benefit host health, and it is feasible to screen and isolate bifidobacteria using the oligosaccharides corresponding to the specific GHs of bifidobacteria as the carbon sources of the selective media.